Measuring Sense of Place: A New Place-People-Time-Self Model - Domingues, Rita B.; Gonçalves, Gabriela; de Jesus, Saúl Neves (Journal of Tourism, Sustainability and Well-being, 2021)
Many models of place attachment and sense of place have proliferated in the last decades, and a consensus on the conceptualisation and operationalisation of these constructs is yet to be reached. We aim to contribute to this discussion, by proposing a new model and measurement of sense of place as an overarching construct, using exploratory and confirmatory analyses. Results suggested that sense of place is a second-order factor with four first-order factors: ‘place’, ‘people’, ‘time’, and ‘self ’. The ‘place’ dimension integrates emotional content associated with the place and can be loosely compared to the unidimensional place attachment in other models. The ‘people’ dimension corresponds to the sense of community construct, whereas the ‘time’ dimension reflects the importance of length of residence and intergenerational transmission. Finally, the ‘self’ dimension is more internally focused than the other dimensions, reflecting the role of the place for an individual’s distinctiveness and self-esteem. Our 32-item Sense of Place Scale is thus a valid and reliable measure based on a quadripartite structure of the sense of place construct.